USING LEATHER PUPPETS AS LOCAL WISDOM BASED LEARNING MEDIAFOR TEACHING THE MATERIAL OF HEREDITY OF THE NATURAL SCIENCESSUBJECT FOR GRADE IX STUDENTS - Yesi Rakhmawati; Putri Apriliani; Merya Wulansari (Pelita - Jurnal Penelitian Mahasiswa UNY, 2013)
The objectives of this study were (1) to reveal the improvement of students’understanding about heredity by using the media of leather puppets, and (2) to findout the use of leather puppets as learning media for teaching heredity to the grade IXstudents.The method used in this study was quasi experiment post test only. The subjectand object of this study were leather puppets as learning media of heredity at gradeIX and the improvement of the students’ understanding about the heredity. About 24students of Wonosari 1 State Junior High School. The data were analyzed throughquantitive analysis.The result of study showed that leather puppets as learning media of herditycould improve the understanding of students from 78.62 ± 4.75 to 79.08 ± 6.29. Thevalue of correlation between leather puppets as learning media and sudents’s markwas 0.0043. It means the value was in the range of 0.00 – 0.2 range. It can be inferredthat there was a correlation between leather peuppets as learning media with thestudents’ understanding.